Vibration Control of Blade Section Based on Sliding Mode PI Tracking Method and OPC Technology - Tingrui Liu (Shock and Vibration)
Vibration control of the blade section of a wind turbine is investigated based on the sliding mode proportional-integral (SM-PI) method, i.e., sliding mode control (SMC) based on a PI controller. The structure is modeled as a 2D pretwisted blade section integrated with calculation of structural damping, which is subjected to flap/lead-lag vibrations of instability. To facilitate the hardware implementation of the control algorithm, the SM-PI method is applied to realize tracking for limited displacements and velocities. The SM-PI algorithm is a novel SMC algorithm based on the nominal model. It combines the effectiveness of the sliding mode algorithm for disturbance control and the stability of PID control for practical engineering application. The SM-PI design and stability analysis are discussed, with superiority and robustness and convergency control demonstrated. An experimental platform based on human-computer interaction using OPC technology is implemented, with position tracking for displacement and control input signal illustrated. The platform verifies the feasibility and effectiveness of the SM-PI algorithm in solving practical engineering problems, with online tuning of PI parameters realized by applying OPC technology.